2011
DOI: 10.1002/cncr.26441
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of zeste homolog 2 is a novel prognostic biomarker in nonsmall cell lung cancer

Abstract: BACKGROUND: Enhancer of zeste homolog 2 (EZH2) epigenetically silences many genes through the trimethylation of histone H3 lysine 27 and is implicated in tumor growth, invasion, and metastasis. However, its role in lung cancer has not been well characterized. The objective of the current study was to elucidate the role of EZH2 in nonsmall cell lung cancer (NSCLC) by investigating both clinical samples and cell lines. METHODS: An immunohistochemical analysis of EZH2 expression was performed in samples from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 31 publications
(31 reference statements)
2
48
0
Order By: Relevance
“…It was reported that EZH2 was found to be overexpressed at both mRNA and protein levels in NSCLC and bladder cancer, and correlated with invasiveness, increased proliferation and poor outcome (20,21). In colorectal cancer, EZH2 overexpression indicated a good prognosis, in contrast to the poor prognosis associated with EZH2 overexpression in NSCLCs (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that EZH2 was found to be overexpressed at both mRNA and protein levels in NSCLC and bladder cancer, and correlated with invasiveness, increased proliferation and poor outcome (20,21). In colorectal cancer, EZH2 overexpression indicated a good prognosis, in contrast to the poor prognosis associated with EZH2 overexpression in NSCLCs (20).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins, together with the histone binding proteins retinoblastoma binding protein 4 (RBBP4) and RBBP7, comprise the core components of the polycomb repressive complex 2 (PRC2). Overexpression of EZH2 was also found in a variety of cancers, including lung cancer (20,21), breast cancer (5,(22)(23)(24)(25)(26), melanoma (27), colorectal (20) and pancreatic adenocarcinoma (28) and ovarian carcinoma (29), and turned out to be closely associated with high proliferation rate and aggressive tumor subgroups, resulting in worse clinical outcome thereafter. Although many reports on the role of H3K27me3 in carcinogenesis are available, its carcinogenic role in NSCLC and how it interacts with EZH2 and DNA methylation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…EZH2 is overexpressed in NSCLC and is associated with poor prognosis (79,80). Similarly overexpression of HDACs has been observed in NSCLC (81).…”
Section: Histone Modification and Chromatin Organizationmentioning
confidence: 92%
“…One such member is EZH2 or KMT6. KMT6 is overexpressed in NSCLC with predictive and prognostic value [1,[9][10][11]. Knockdown of KMT6 has been shown to inhibit NSCLC proliferation, migration and invasion [9,10].…”
Section: "New Studies Involving 'Low-dose'mentioning
confidence: 99%
“…KMT6 is overexpressed in NSCLC with predictive and prognostic value [1,[9][10][11]. Knockdown of KMT6 has been shown to inhibit NSCLC proliferation, migration and invasion [9,10]. Overexpression of KMT6 occurs in cisplatin-resistant cell lines and knockdown results in enhanced sensitivity to cisplatin [10].…”
Section: "New Studies Involving 'Low-dose'mentioning
confidence: 99%